(untitled) (REMUNOM, 2024)
The research addresses the applicability of the principle of insignificance in cases of repeat offenders. Through a bibliographical review, analysis of legislation and jurisprudential analysis. Firstly, it addresses the historical and doctrinal origin of the principle, conceptualizing and demonstrating the application conditions established and pacified by jurisprudence. Examines the typicality and legal nature of the principle. Analyzes the conditions that affect the application or that make it impossible to apply. Concluding with an analysis of the understanding of the higher courts regarding the application and mitigations to the principle.